The Cytoxic Effects Of Forest Honey (Apis dorsata) On T47D Breast Cancer Cells - Adnan, Malik Hisyam; Rakhmawatie, Maya Dian; Tursinawati, Yanuarita (Universitas Muhammadiyah Semarang, 2024)
Background: In 2018, an estimated 2 million people had breast cancer. Forest honey (Apis dorsata) can have antioxidant activity due to the presence of flavonoid saponin, alkaloid, and tannin compound, therefore can be used as anticancer through the induction of apoptosis.Objective: To determine the IC50 of forest honey (Apis dorsata) on T47D breast cancer cells and see the morphology of T47D cells after administration of forest honey.Methods: This study is an in vitro test of the cytotoxic activity of forest honey against T47D breast cancer cells using the MTT assay method. The concentration of forest honey was prepared by the two-fold microdilution method in the range of 1000 - 31.25 µg/mL. Doxorubicin was used as a control drug with a concentration of 20 - 0.675 µg/mL. The morphology of T47D cells after treatment was observed with an inverted microscope with 400x magnification.Results: Forest honey (Apis dorsata) from any concentration did not show any inhibition of growth of T47D breast cancer cells. Meanwhile, doxorubicin had an IC50 of 3.746 µg/mL. The morphology of T47D cells with honey administration showed many live cells with formazan crystals.Conclusion: Forest honey has no cytotoxic activity against T47D breast cancer cells.